Erythrolamprus miliaris orinus (Reptilia, Squamata, Dipsadidae): predation attempts on Boana faber and Leptodactylus latrans (Amphibia, Anura) - Rocha-Lima, Ana Beatriz Carollo; Santos, Isaías; Duarte, Letícia Suigh Carlos; da Costa, William Pinheiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
This communication reports two predation attempts involving subadults of the snake Erythrolamprus miliaris orinus on two species of large anurans, as well as the possible strategies of the snake in the face of difficulty to ingest the prey individual. In both cases, amphibians were successful in escaping the predator. The fact that the two individuals were relatively large (between 60 and 70 mm snout-vent length) compared to most amphibians possibly favored the escape, as well as the withdrawal of the snake in effecting the predation. The strategies reported here, in some cases, can increase predation efficiency when the prey is relatively large or resistant. The type of substrate, the size relation between prey and predator and the experience of the snake also can be limiting factors to determine the efficiency of capture.